The Two Rainbow Serpents Travelling Mura track narratives from the 'Corner Country' - Beckett, Jeremy (Aboriginal History Monographs, 2009)
The 'Corner Country', where Queensland, South Australia and New South Wales now converge, was in Aboriginal tradition crisscrossed by the tracks of the mura, ancestral beings, who named the country as they travelled, linking place to language. Reproduced here is the story of the two Ngatyi, Rainbow Serpents, who travelled from the Paroo to the Flinders Ranges and back as far as Yancannia Creek, where their deep underground channels linked them back to the Paroo. Jeremy Beckett recorded these stories from George Dutton and Alf Barlow in 1957. Luise Hercus, who has worked on the languages in the area for many years, has collaborated with Jeremy Beckett to analyse the names and identify the places.